CO2 Enrichment Differentially Upregulated Sugar, Proline, and Polyamine Metabolism in Young and Old Leaves of Wheat and Sorghum to Mitigate Indium Oxide Nanoparticles Toxicity - Shabbaj, Ibrahim I.; Madany, Mahmoud M. Y.; Balkhyour, Mansour A.; Tammar, Abdurazag; AbdElgawad, Hamada (Frontiers in Plant Science, 2022)
Soil contamination with indium oxide nanoparticles (In2O3-NPs) is a challenge for plant growth and productivity. Despite In2O3-NPs toxicity, their effects on plants growth and metabolism are largely unknown, particularly under future climate CO2 (eCO2). Therefore, In2O3-NPs toxicity and stress mitigating impact of eCO2 in the young and old leaves of C3 (wheat) and C4 (sorghum) plants. Overall, In2O3-NPs significantly retard the biomass and photosynthetic machinery of all tested crops, particularly the young leaves of C3 plants. Consequently, In2O3-NPs altered C and N metabolism in C3 and C4 plants. On the other hand, eCO2 contrarily alleviated the hazardous effects of In2O3-NPs on growth and photosynthesis, especially in the young leaves of C4 plants. Increased photosynthesis consequently enhanced the soluble sugars accumulation and metabolism (e.g., sucrose P synthase, cytosolic and vacuolar invertase) in all stressed plants, but to more extent in C4 young leaves. High sugar availability also induced TCA organic and fatty acids accumulation. This also provided a route for amino acids and polyamines biosynthesis, where a clear increase in proline biosynthetic enzymes (e.g., pyrroline-5-carboxylate synthetase (P5CS), ornithine aminotransferase (OAT), Pyrroline-5-carboxylate reductase (P5CR), pyrroline-5-carboxylate dehydrogenase (P5CDH), and proline dehydrogenase (PRODH)) and polyamine metabolic enzymes (e.g., spermine and spermidine synthases, ornithine decarboxylase, adenosyl methionine decarboxylase) were mainly recorded in of C4 young leaves. The observed increases in these metabolites involved in osmo- and redox-regulation to reduce In2O3-NPs induced oxidative damage. Overall, our study, for the first time, shed the light on how eCO2 differentially mitigated In2O3-NPs stress in old and young leaves of different species groups under the menace of In2O3-NPs contamination.